Data sleuth : using data in forensic accounting engagements and fraud investigations - Wietholter, Leah (Wiley corporate F & A series., 2022)
"In Data Sleuthing: Using Data in Forensic Accounting Engagements and Fraud Investigations, forensic accounting engagements are simplified into a step-by-step Data Sleuth TM process that can be applied to almost any project while maintaining reliable, trustworthy results. When Wietholter first joined the forensic accounting and fraud investigation industry, other experts would provide training on theories but not hands-on application and processes. As she gained more experience and grew her practice, she looked to fill this gap in training and make her services available to more people. In doing so, she developed the Data Sleuth TM process to simplify and streamline forensic accounting engagements and investigations. Through this book, she would like to share this process so others can start their own practices, empower their teams, and ultimately make investigations more accessible. The Data Sleuth TM approach emphasizes the use of best evidence while working through problem-solving techniques to address the challenges of imperfect information. By using the Data Sleuth TM process in investigations, accountants and investigators will improve the quality of their work products resulting in more opportunities for mediations and settlements. This approach also allows accountants and investigators to increase capacity and grow their businesses, helping more clients find missing money. Data Sleuthing will cover topics such as: What is data sleuthing? Why is data sleuthing necessary? How does data sleuthing fit into forensic accounting and fraud investigations? Data sleuthing framework Applying the data sleuth framework to real world cases"--